Android-Based Wedding Planner Application System Design (Case Study: Nawasena Organizer) - Ipnuwati, Sri; Wardana, Yusril Izza; Mandala, Sri Surya (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
In an era of increasingly rapid technological development, the need for information is very important for society. With advances in technology, people are able to access the information they need quickly and accurately. Technological advances are also starting to enter various business fields. Usually, technology in the business sector is used as a marketing medium with a wider reach to attract the interest of potential consumers. Applications are a form of technological and informational progress that makes it easier for the public and business actors to access or disseminate information. One of them is a wedding planner application. This application can provide information or an overview of what is needed in the wedding procession. Nawasena Organizer is a wedding planner service provider. Nawasena itself still uses social media methods to communicate with customers. Because it is still quite complicated when it comes to explaining what services are available, communication between admin and customers takes a long time because there are many things that have to be explained directly. For this reason, a wedding planner application system is designed to make it easier for customers to find out all the information about wedding services. This wedding planner application is planned to be built on the Android operating system, which is a system that is very commonly used by all levels of society.